New Challenges in Neutrosophic Theory and Applications - Vladutescu, Stefan; Colhon, Mihaela (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Neutrosophic theory has representatives on all continent sand, therefore, it can be said to be a universal theory. On the other hand, according to the two volumes of "The Encyclopedia of Neutrosophic Researchers" (2016, 2018) about 150 researchers from 37 countries apply the idea and the neutrosophic method. Neutrosophic theory was founded by Professor Florentin Smarandache in 1998; it constitutes further generalization of fuzzy and intuitionistic fuzzy theories. The key distinction between the neutrosophic set/logic and other types of sets/logics consists of the introduction of the degree of indeterminacy/neutrality (I) as independent component in the neutrosophic set. Thus, neutrosophic theory involves the degree of membership-truth (T), the degree of indeterminacy (I), and the degree of non-membership-falsehood (F). In recent years, the field of neutrosophic set, logic, measure, probability and statistics, precalculus and calculus etc. and their applications in multiple fields have been extended and applied in various fields, such as communication, management and information technology. The present volume gathers the latest neutrosophic techniques, methodologies or mixed approaches, being thus a barometer of the neutrosophic research in 2020.